Exerting Self‐Control ≠ Sacrificing Pleasure - Vosgerau, Joachim; Scopelliti, Irene; Huh, Young Eun (Journal of Consumer Psychology, 2020)
Self‐control is a prominent topic in consumer research, where it is often conceptualized as the abstinence from hedonic consumption. We examine whether this conceptualization accurately captures consumers’ experiences of self‐control conflicts/failures in light of seminal self‐control theories in economics and psychology. Rejecting that notion, we argue that self‐control failures are choices in violation of superordinate long‐term goals accompanied by anticipated regret, rather than choices of hedonic over utilitarian consumption. This conceptualization has important methodological, theoretical, and practical implications. Methodologically, it highlights the need for experimental paradigms with higher construct validity. Theoretically, it helps elucidate how self‐control is distinct from impatience and self‐regulation. Practically, it provides a rich set of implications for deducing interventions on the individual and public policy level to help consumers exert self‐control.